Complicated but Crucial: Higher Education’s Missions for the Labor Market - Altbach, Philip; de Wit, Hans (International Higher Education, 2024)
Higher education has many and varied missions and purposes. It has from the beginning been engaged in what we now call “workforce training,” including preparing students for the professions. But universities have also provided a broader curriculum in the liberal arts and for critical thinking. Current emphasis on the labor market should not ignore the broader aims of postsecondary education.